2011
DOI: 10.5358/hsj.30.177
|View full text |Cite
|
Sign up to set email alerts
|

Development of Microsatellite Markers for the Two Giant Salamander Species (Andrias japonicus and A. davidianus)

Abstract: The Japanese giant salamander (Andrias japonicus) is a near threatened species endemic to western Japan and is strictly protected by law. However, available information regarding the genetic diversity and genetic structure in this species, essential for its effective conservation, has been limited. We developed four microsatellite markers from A. japonicus and characterized these markers for two populations of this species, as well as for some captive Chinese giant salamanders (A. davidianus) of unknown origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Despite the significant threats facing the species and recent dramatic declines, the molecular ecology of the Chinese giant salamander is still relatively poorly understood. Microsatellite loci (Yoshikawa et al 2011;Meng et al 2012) and a full mitochondrial genome (Zhang et al 2003) have been developed for the species, but thus far population genetic work on Chinese giant salamanders has mainly focused on geographic patterns of variation in proteins and single mitochondrial genes. One study examined 40 allozymes and two mitochondrial genes in 19 individuals to assess variation and population structure among nine locations across much of the current range of the species (Murphy et al 2000).…”
Section: Amphibian Conservationmentioning
confidence: 99%
“…Despite the significant threats facing the species and recent dramatic declines, the molecular ecology of the Chinese giant salamander is still relatively poorly understood. Microsatellite loci (Yoshikawa et al 2011;Meng et al 2012) and a full mitochondrial genome (Zhang et al 2003) have been developed for the species, but thus far population genetic work on Chinese giant salamanders has mainly focused on geographic patterns of variation in proteins and single mitochondrial genes. One study examined 40 allozymes and two mitochondrial genes in 19 individuals to assess variation and population structure among nine locations across much of the current range of the species (Murphy et al 2000).…”
Section: Amphibian Conservationmentioning
confidence: 99%
“…In contrast to the observed reduced genetic diversity in mtDNA, A. japonicus might actually have yet uncovered genetic diversification. For example, we may recover loci that display polymorphism in sequences containing microsatellite repeats (Yoshikawa et al, 2011(Yoshikawa et al, , 2012, although Chen et al (2012) found extreme genetic uniformity among populations of Ranodon sibiricus in not only mtDNA but also microsatellites. Similarly, amplified fragment length polymorphism (AFLP) analyses would show genetic diversities, although the results may be difficult to interpret .…”
Section: Discussionmentioning
confidence: 99%
“…To identify the introduced Chinese giant salamanders and hybrids, we used microsatellite markers developed for giant salamanders 24 , 25 . For reference data, we collected Japanese and Chinese giant salamanders in Japan (Table 2 , Fig.…”
Section: Methodsmentioning
confidence: 99%